Experimental and Numerical Investigations of Pressure Field of Curved Shell Structure Subjected to Interior Blast - Jialu Ma; Feng Fan; Lingxin Zhang; Chengqing Wu; Xudong Zhi (Shock and Vibration)
A terrorist attack on a long-span spatial structure would cause horrible results. Therefore, it is important to determine the characteristics of blast pressure fields to protect such structures. In this study, fully confined blast loading tests were conducted using a rigid curved shell model, which had an inner space similar to that of a reticulated dome. Four different scenarios were carried out to record the blast loading on five typical positions. The blast pressure-time data were compared and analyzed. In addition, a suitable numerical simulation method was proposed for the issues involved in interior blast loading. This numerical model was verified by comparing with the test data. A parametrical analysis of the interior blast simulations was conducted based on this numerical method. The blast loading values at specific positions were obtained with the key parameters varied within a reasonable scope. The blast loading from blast tests and simulations were presented. On this basis, the interior blast loading could conveniently be predicted by using the method and data in this paper, which could be used in the protective design of other reticulated domes.